The current global recession : a theoretical and empirical investigation into developed and BRICS economics - Prabhakar, Akhilesh Chandra (Emerald Group Publishing Limited, 2016)
This generation's economic crisis has truly global reach, with repercussions reverberating throughout nations and across societies. Prabhakar investigates the world-wide depression, using empirical understanding and new data sets on indicator and policy variables. He focuses on: the overall causes of this crisis and the failures of mainstream economics; analyzes the rising tide of poverty and social inequality resulting from the depression; examines the relationship between the economic crisis and economic systems; studies the evolution of the global monetary system and history of central banking; and delves into BRICS with a particular focus on China and India, as well as Europe and the United States. This applicable work should be used to understand and study the true global reach of this crisis, and the effect on economic policy and society as a whole.